Temporal binding and sense of agency in major depression - Vogel, David H. V.; Jording, Mathis; Weiss, Peter H.; Vogeley, Kai (Frontiers in Psychiatry, 2024)
Background: Alterations in the experience of controlling oneself and one's environment are of high relevance to understanding the psychopathology of depression. This study investigated the relationship between TB for action-event sequences, SoA, SE and symptom severity in MDD.We employed the Sense of Agency Scale (SoAS) and the General Self-Efficacy Scale (GSE) to assess explicit SoA and SE in a group of 42 persons diagnosed with MDD (20 identifying as female, 19 as male; mean age 37.8 years (±13.3)) and 40 control persons without a psychiatric diagnosis (CG) (22 identifying as female, 20 as male; mean age 38.0 years (±13.3)). Depressive symptom severity was measured using the BDI-II. We additionally performed a TB paradigm as a potential correlate to SoA. Participants partook in a time estimation task judging three intervals (250ms, 450ms, 650ms) while either observing or causing stimulus presentations. The underestimation of intervals following intentional actions causing stimulus presentations (compared to merely observing the stimulus presentation) is interpreted as TB.Results:SoAS scores demonstrated an inverse correlation with depressive symptoms (CG: p=.032, R 2 =.113; MDD: p<.001, R 2 =.260) and a positive correlation with GSE scores (CG: p<.001, R 2 =.379; MDD: p<.001, R 2 =.254). We found distinct differences in TB between healthy participants and the MDD group without significant correlation between TB and the SoAS or GSE scores. The data suggest group differences in time estimation particular pertaining to time intervals involving intentional action and increasingly complex multisensory stimuli.Discussion: We investigated parameters of subjective control, namely SoA and SE. Here, we were able to reveal their inverse relationship with depressive symptoms in patients with MDD, highlighting a profound experience of loss of control with increasing symptom load. Deficits in experiencing control, particularly involving intentional motor actions (and more complex multisensory stimuli), appear to be more pronounced in MDD, involving not only negative self-efficacy expectations but also an altered SoA and TB. TB and SoAS scores did not correlate, adding to the growing evidence that the two measures may not be directly related. We propose that future research be directed at this contiguous relationship between SoA and SE in MDD.